The Effect of Customer Relationship Management on Customer Loyalty at Chat Barber Banjarmasin - Orion Yoga Pratama; Sugiharto; M. Hasanur Arifn; Setio Utomo (Magister Administrasi Bisnis ULM, 2025)
This study aims to examine the partial effect of Customer Relationship Management on customer loyalty at Chat Barber Banjarmasin. This research employs a quantitative approach. The sample consists of 71 Chat Barber customers who met the predetermined criteria, selected using a non-probability sampling technique, namely incidental sampling. Data were collected through questionnaires, and data analysis was conducted using simple linear regression analysis. The results indicate that Customer Relationship Management (CRM) has a significant partial effect on customer loyalty